ASUHAN KEPERAWATAN MASALAH PSIKOSOSIAL HARGA DIRI RENDAH SITUASIONAL PADA NY. E DENGAN POST OPERASI FRAKTUR FEMUR DI WILAYAH LIMO KELURAHAN LIMO KOTA DEPOK. - Andira Kurnia Suhendi (2023)
Background: Fractures occur in musculoskeletal diseases that can cause problems on quality of life such as changes in body image, the inability to perform daily activities, and the incapacity to take care of themselves because the quality of a person's life is considered low. The average outcome of patients with postoperative femoral fracture quality is good, except for patients whose survival and quality of life are still very low, as well as negative feelings or feelings of invaluability, inability to take responsibility for their own lives, or low self-esteem. Chronic low self-esteem is a long-lasting negative feeling toward oneself, that is, before and after being treated, and situational low self appreciation is a negative assessment or feeling about oneself or the ability of the client in response to the current situation. The study of this case study was conducted to understand the Assumption of nursing in Ny. E who has experienced psychosocial problems of low self-esteem situation with post-operative fracture of the femur in the limo limo area of the city of Depok. Research method: The research method is a case study. Research Results: The nursing problem that arises is situational low self-esteem by carrying out an implementation strategy by developing the positive aspects that the patient has and then developing them together to help increase the patient's self-confidence. Conclusion: Treatment of Nurses at N. E with a low psychosocial self-esteem problem situationally achieves the expected results, where the patient cooperates during the action, a favorable environment during the activity, then begins to be open to the story of his problem with the nurse.